Odpowiedź:
[tex]a_{1}[/tex]= [tex]\frac{1}{5}[/tex] (4*1-7)
[tex]a_{1}\\[/tex]= [tex]\frac{1}{5}[/tex] * (-3)
[tex]a_{1}\\[/tex]= -[tex]\frac{3}{5}[/tex]
[tex]a_{2}[/tex] = [tex]\frac{1}{5}[/tex] (4*2-7)
[tex]a_{2}[/tex] = [tex]\frac{1}{5}[/tex] * 1
[tex]a_{2}= \frac{1}{5}[/tex]
[tex]a_{3}[/tex] = [tex]\frac{1}{5}[/tex] (4*3-7)
[tex]a_{3}[/tex] = [tex]\frac{1}{5}[/tex] * 5
[tex]a_{3}[/tex] = 1
r= [tex]a_{2} -a_{1}[/tex]
r= [tex]\frac{1}{5} - (- \frac{3}{5} )[/tex]
r= [tex]\frac{4}{5}[/tex]
r= [tex]a_{3} - a_{2}[/tex]
[tex]\frac{5}{5} - \frac{1}{5} = \frac{4}{5}[/tex]
Ten ciąg jest arytmetyczny